Deteksi Bakteri Salmonella spp Dan Pengujian Kualitas Telur Ayam Buras - NUGRAHA, ADITYA; SWACITA, IDA BAGUS NGURAH; TONO P.G, KETUT (Indonesia Medicus Veterinus, 2012)
The purpose of this research is to know the contaminan of bacterium of Salmonella spp. and the quality of local chicken eggs wich sold at Kuta I, Kuta II, Jimbaran, and Kedonganan traditional market. Sample of this research were taken from 120 local chicken eggs from four randomized traditional market. After ward each and every sample were inoculated at Tetrathionate Broth media, then streaked at Salmonella Shigella Agar (SSA) media. If a colony on SSA media appeared to be convex, transparant, with or without black spot at central shares, after that will be continued with Gram stain and biochemistry test covering cultivation at media of TSIA, IMViC. The result, from 120 sample of local chicken eggs which is sold in Kuta I, Kuta II, Jimbaran, and Kedonganan traditional market indicated that were no containing Salmonella spp. and the quality of local chicken eggs wich sold at Kuta I, Kuta II, Jimbaran, and Kedonganan traditional market significantly different (P <0.05) evaluated from the albumin Index , but not significantly different (P> 0.05) when viewed from the York index.
Keywords: Salmonella spp, albumin index, york index, local chicken egg, tradisional market.